The Role Of Educators In Instilling Religious Values In Early Childhood AT TPQ Insan Robbani Al-Fikri - Darmawan, Dadan; Alika, Putri; Ganiadi, Mochamad (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2025)
Education is an important factor in building an intelligent nation. Through educators, it becomes a conscious human effort to enhance knowledge, skills, and even personality development. The aim of this research is to instill religious values in early childhood at TPQ Insan Robbani Al-Fikri, Tangerang City, through the role of educators as facilitators and parents as role models. The research method used is a descriptive qualitative approach. Data collection techniques include interviews, observations, and documentation. This research was conducted at TPQ Insan Robbani Al-Fikri in Kp. Karang Anyar, Neglasari Sub-district, Tangerang City. The results of this research show that educators who act as facilitators have five indicators of success: (1) the provision of learning tools has been adequately implemented, (2) the availability of learning facilities, including methods, media, and equipment, is fairly complete, (3) educators act as companions to students, (4) educators fulfill their duties and functions in accordance with regulations, and (5) educators do not act arbitrarily towards students. Thus, the role of educators as facilitators and the role of parents as effective role models contribute significantly to shaping the religious character of early childhood, particularly in aspects of worship, prayer, and behavior in accordance with religious teachings.